The EFFECTIVENESS OF APPLICATION OF BINAHONG LEAF (ANREDERA CORDIFOLIA) BOILED WATER AS A THERAPY FOR ACNE VULGARIS - Reffita, Lea Ingne (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Traditional medicine has been used by various aspects of society from the upper to lower economic levels, one of the medicinal plants that is widely known by the Indonesian people but has prospects as a source of medicinal ingredients is binahong with the scientific name Anredera cordifolia. The binahong leaves are boiled and then applied to respondents who have moderate acne, aged 17-24 years. The purpose of this study was to determine the effect of the application of boiled water from the leaves of binahong (Anredera cordifolia) as a treatment for acne vulgaris. This research method is experimental. How to collect data with questionnaires, documentation and observation. Data analysis using T-test. The sample in this study were students of the Faculty of Health Sciences, University of Ibrahimy, aged 17-24 years who had moderate acne types, with a total of 30 respondents. The variable in this study was the boiled water of binahong leaves packaged in a spray bottle. The average value before treatment is while the value after being given treatment. Based on research that boiled water from binahong leaves has a significant effect on respondents to reduce the number of acne lesions. Based on the hypothesis test, it is known that the correlation coefficient value is 0.796 with p value (sig) 0.000 <0.05, then H0 is rejected and Ha is accepted.